Detection of paternal origin of fetal trisomy 18 in a pregnancy conceived by assisted reproductive technology and in vitro fertilization - Chih-Ping Chen; Schu-Rern Chern; Liang-Kai Wang; Shin-Wen Chen; Fang-Tzu Wu; Dai-Dyi Town; Wayseen Wang (Taiwanese Journal of Obstetrics & Gynecology, 2020)
Objective: We present detection of paternal origin of fetal trisomy 18 in a pregnancy conceived by assisted reproductive technology (ART) and in vitro fertilization (IVF). Case report: A 39-year-old woman underwent ART and IVF because of primary infertility. The woman was infertile because of myoma and endometriosis. Her husband was 39 years old, and the sperm analysis was normal. The couple was phenotypically normal. This pregnancy was conceived successfully by IVF. She received non-invasive prenatal testing at 11 weeks of gestation, the result showed a high risk for trisomy 18. She underwent chorionic villus sampling at 12 weeks of gestation, and the result was 47,XY,+18 in 24/24 cultured chorionic villi cells. Prenatal ultrasound findings were unremarkable. She underwent amniocentesis at 17 weeks of gestation, and the result was 47,XY,+18 in 20/20 colonies of cultured amniocytes. The pregnancy was subsequently terminated. Postnatal cytogeneic analysis confirmed the prenatal diagnosis. Polymorphic DNA marker analysis on the DNAs extracted from the umbilical cord and parental bloods showed a paternal origin of the extra chromosome 18, indicating a paternal origin of fetal trisomy 18. Cytogenetic analysis of paternal blood revealed a karyotype of 46,XY. Conclusion: Fetal trisomy 18 in pregnancies conceived by ART may be of paternal origin, and determination of paternal origin by polymorphic DNA marker analysis is useful for genetic counseling under such a circumstance.